2020
DOI: 10.1021/jacs.0c08427
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of an Organocatalytic Cope Rearrangement Involving Iminium Intermediates: Elucidating the Role of Catalyst Ring Size

Abstract: The mechanism of the organocatalytic Cope rearrangement is elucidated through a combined computational and experimental approach. As reported previously, hydrazides catalyze the Cope rearrangement of 1,5-hexadiene-2-carboxaldehydes via iminium ion formation, and seven- and eight-membered ring catalysts are more active than smaller ring sizes. In the present work, quantum mechanical computations and kinetic isotope effect experiments demonstrate that the Cope rearrangement step, rather than iminium formation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Microdynamic model analysis has been shown to be a helpful tool for analyzing the competing reaction networks in homogeneous catalysis. 89–97 The Eyring–Polanyi equation 98 was used to obtain the reaction rate constant k .where κ is the transmission factor, which was assumed to be 1.0 in homogeneous catalysis, k B is the Boltzmann constant, T is the temperature, h is the Planck constant, R is the ideal gas constant, and Δ G ≠ is the activation free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Microdynamic model analysis has been shown to be a helpful tool for analyzing the competing reaction networks in homogeneous catalysis. 89–97 The Eyring–Polanyi equation 98 was used to obtain the reaction rate constant k .where κ is the transmission factor, which was assumed to be 1.0 in homogeneous catalysis, k B is the Boltzmann constant, T is the temperature, h is the Planck constant, R is the ideal gas constant, and Δ G ≠ is the activation free energy.…”
Section: Resultsmentioning
confidence: 99%
“…The firstly developed organocatalyzed Cope rearrangement was reported in 2016 by the Gleason's group (Scheme 35) [75,76] in the synthesis of α-substituted enals 168 from 1,5-hexadienyl-2-carboxyaldehydes 167, using the pair hydrazide 148/ TfOH as the catalyst. The reaction mechanism was elucidated through DFT calculation [77]. The authors found that the 7-membered hydrazide catalyst 169 was ten times more reactive than its 6-membered homologous.…”
Section: Organocatalyzed Cope Rearrangementmentioning
confidence: 99%
“…Consequently, a correlation between the transition-state geometry and experimental KIEs has been well established . This combined experimental and theoretical approach has led to the resolution of several highly debated reaction mechanisms in organic chemistry …”
Section: Introductionmentioning
confidence: 99%